Implementasi Sistem Pengendalian Manajemen Dalam Meningkatkan Efektivitas Kerja Pegawai Pada Badan Nasional Penanggulangan Terorisme Republik Indonesia - Siti Hutami Hariati M (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2023)
Implementation of Management Control Systems in Improving Employee Work Effectiveness at the National Counterterrorism Agency of the Republic of Indonesia (supervised by Mursalim and Fadliah Nasaruddin). The aims of this study were to determine (1) the adequacy of the management control system (SPM) implementation, and (2) the SPM's role in increasing the effectiveness of the work of employees at the National Counterterrorism Agency (BNPT) of the Republic of Indonesia. This study uses primary data, namely through the distribution of questionnaires. The research methodology used is a qualitative descriptive analysis method. Testing the data using questionnaire answers with a sample consisting of 210 civil servants and TNI/POLRI, 83 PTT and 17 task units of the BNPT of the Republic of Indonesia. Based on the results of the questionnaire testing, it was concluded that the adequacy of the implementation of SPM at the BNPT of the Republic of Indonesia was very adequate. And, the role of SPM in increasing the work effectiveness of employees at the BNPT of the Republic of Indonesia, is very important.